ORGANIC VEGETABLES SUPPLY CHAIN CHARACTERISTICS OF SMALL ENTERPRISES IN MALANG - Neza Fadia Rayesa (Socio-Economics/Agribusiness Department, 2022)
Supply chain is a valuable and strategic decision even for small enterprises. This research aimed to identify the supply chain characteristic of small enterprises in Malang. Data and information were collected through observation and in-depth interviews based on business processes in the SCOR model. The result shows that small organic farming already has a strong relationship between stakeholders. However, the research found a lack of traceability for organic input, unstable production due to some situations, and a limited served market.